Reclaiming History from the Settler Coloniser: A Meditation on Nur Masalha's Palestine across Millennia: A History of Literacy, Learning and Educational Revolutions. Issue 1 (April 2023) - Docker, John
Abstract : In this wonderful book, Nur Masalha challenges and transforms world history, as did his earlier Palestine: A Four Thousand Year History (2018). In this meditation I recount some of Nur Masalha's argument — not all, given the extraordinary richness of the material he has uncovered, described, and analysed — but also offer my own reflections prompted by his book. As Masalha relates in his introduction, the work is a passionate response to Zionism's historical claim that Palestinians possess no history of literacy, education, and literary culture. He shows the falsity of such a claim through multiple examples. Masalha explores, for example, the multifaceted history of education in Byzantine Palestine (Third to Early Seventh Century), based on a philosophy of 'civil society'. Palestine as a cosmopolitan and transnational world inhered in what Masalha refers to as Cities of Learning. There were famous intellectuals, such as in antiquity Josephus (AD 37-c.100) and Origen (AD 185–253). In modernity he highlights Khalil Sakakini (1878–1953), whose remarkable educational reforms, emphasizing a 'philosophy of joy', emerged at a similar time to A.S. Neill's Summerhill School in the UK. Women's education is featured, from the time of the Palestinian Madrasas under the Ayyubids and Mamluks (1187–1517) onwards, a powerful tradition which continues into the modern era. When press censorship was relaxed following the Ottoman Young Turk Revolution of 1908, there was a huge growth of newspapers, photography, and photojournalism, a remarkable figure here being the Palestinian photographer Karima 'Abboud (1893–1940). Masalha draws attention to the importance of translation in Palestinian history, especially in the important figure of Khalil Ibrahim Beidas, a relative of Edward Said, who was interested in the works of Pushkin, Gogol, Dostoevsky, Tolstoy and Gorky. There is a fascinating chapter on the interactions of Palestinian scholars and the Crusaders, with free passages of ideas, goods and technologies; arabesque became a mainstream European decorative art. The result of these multiple explorations is a major transformation in how we think about the world.